Analysis of Security and Data Protection Aspects of DPJP (Dokter Penanggung Jawab Pelayanan) Digital Signatures in Electronic Medical Records (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The enhancement of security for electronic medical record data has become a primary concern for both users and application developers, given the sensitive nature of patient information and the increasing adoption of digital healthcare systems. Digital signatures in electronic transactions play a critical role in authenticating the identity of the signer and ensuring the integrity and authenticity of electronic information. In Indonesia, several hospitals have implemented digital signatures, including Tk III 04.06.03 Dr. Soetarto Hospital Yogyakarta, RSUP Hasan Sadikin, and Haji Makassar Hospital. At Haji Makassar Hospital, electronic medical records were first implemented in outpatient services in November 2023, followed by inpatient services in August 2024, and the emergency department (ED) in July 2024. Alongside this implementation, digital signatures for healthcare professionals were introduced. However, the current application only includes signatures from the Responsible Physician (Dokter Penanggung Jawab Pelayanan/DPJP) and ED nurses, represented in the form of QR barcodes, which have not yet been certified by an authorized certification authority. The objective of this study is to analyze the security and data protection aspects of DPJP digital signatures in electronic medical records at RSUD Haji Makassar. Using a descriptive qualitative method with a phenomenological approach, data were collected through purposive sampling techniques, focusing on the perceptions and experiences of relevant stakeholders. The findings indicate that while the current digital signature system used by DPJP at RSUD Haji Makassar provides adequate security and data protection measures to prevent unauthorized access or data tampering, the lack of formal certification poses a limitation in terms of legal validity. To strengthen trust, compliance, and legal standing, it is recommended that RSUD Haji Makassar immediately pursue certification for DPJP digital signatures in accordance with national electronic transaction regulations. This step would ensure that electronic medical records not only meet operational and security needs but also fulfill legal requirements for authenticity and accountability in digital health documentation.